Anthropological sketch of the prehistoric population of the Carpathian Basin - Zoffmann, Zsuzsanna K. (Acta Biologica Szegediensis, 2000)
The present review is an attempt to sketch the anthropological characteristics of the populations that inhabited the smaller or larger geographical units of the whole Carpathian Basin during the several thousand years of prehistory in a grouping according to archaeological cultures defined up to now (which are constantly modified and precised) based on taxonomic data in the technical literature and the results of my Penrose-analyses that attest to the continuity of the autochtonous populations.